Editorial - Thomas, Joby (Atna Journal of Tourism Studies, 2012)
Atna-Journal of Tourism Studies (ATJS) has now entered its eighth year of publication and has become a major venue for the rapid publication of high quality articles on research and learning in tourism. ATJS has continued to make progress in terms of publishing peer-reviewed articles and has attracted an ever increasing national audience of authors, research investigators, and scholars, as indicated by the increasing number of submissions and published papers. To accommodate the growing interest this year onwards the Journal will be published bi-annually. This has only been possible due to the large number of high quality submissions and the invaluable contribution of the reviewers, without whom we would be unable to function. We are very grateful to all the authors and reviewers for helping AJTS become known to the travel and tourism community in India and beyond